Hubungan Kualitas Pelayanan, Citra Sekolah, Kepuasan Siswa dan Loyalitas Siswa (Studi Empirik di SMK Negeri Rembang, Pasuruan, Jawa Timur) - Khusaeni, Akhmad (Jurnal Aplikasi Manajemen, 2016)
Service schools Â rated excellent if the quality of service and teaching in schools to meet the desires, expectations and needs of students. In addition to the quality of service, satisfaction is also influenced by the image of the school itself.Student satisfaction will generate the loyalty.Loyalty of students indicated with the delivery of positive word of mouth about school services, giving recommendations to the younger generation of the school of origin and family to study at the same school.This study aims to determine the loyalty of students in SMK Rembang Pasuruan, with the factors that influence it, that is quality of service, school's image, and student satisfaction. This study is a quantitative empirical research. The data were obtained from 200 students in SMK Rembang Pasuruan.Analysis of the data used is Partial Least Square (PLS) with PLS-Path Modeling (PLS-PM)method.The results of the research are: first, the services quality of school to students nearly met.The higher the quality of service caused the higher student satisfaction.Second, the school's image in the eyes of the students has been good. The highschool's image makes the student be satisfied to learn in school and the school's image also directly affectto student loyalty.Third, student satisfaction are lacking.Student satisfaction does not affect to student loyalty.